2000
DOI: 10.1002/(sici)1097-4601(2000)32:1<52::aid-jck6>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the Ce(III)-, Mn(II)- or Fe(phen)32+-catalyzed Belousov-Zhabotinsky reaction with ethyl hydrogen malonate

Abstract: In a stirred batch reaction, Fe(phen) 3 2ϩ ion behaves differently from Ce(III) or Mn(II) ion in catalyzing the bromate-driven oscillating reaction with ethyl hydrogen malonate [CH 2 COOHCOOEt, ethyl hydrogen malonate (EHM)]. The effects of N 2 atmosphere, concentrations of bromate ion, EHM, metal ion catalyst, sulfuric acid, and additive (bromide ion or bromomalonic acid) on the pattern of oscillations were investigated. The kinetic study of the reaction of EHM with Ce(IV), Mn(III), or Fe(phen) 3 3ϩ ion indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Smoes first studied the effects of the initial sulfuric acid concentration on the period time of the iron-catalyzed BZ reaction and showed that the period time decreases exponentially with increasing acidity in the range 0.3–1.4 mol L –1 H 2 SO 4 . A decrease in the period time with increasing acidity was also reported for the cerium-catalyzed reaction by Misra et al with initial H 2 SO 4 concentrations up to 4.0 mol L –1 and by Hsu and Jwo in the acidity range 0.5–1.5 mol L –1 H 2 SO 4 . The acid dependence usually has been associated with the bromine chemistry of reactions R1–R5.…”
Section: Introductionmentioning
confidence: 75%
“…Smoes first studied the effects of the initial sulfuric acid concentration on the period time of the iron-catalyzed BZ reaction and showed that the period time decreases exponentially with increasing acidity in the range 0.3–1.4 mol L –1 H 2 SO 4 . A decrease in the period time with increasing acidity was also reported for the cerium-catalyzed reaction by Misra et al with initial H 2 SO 4 concentrations up to 4.0 mol L –1 and by Hsu and Jwo in the acidity range 0.5–1.5 mol L –1 H 2 SO 4 . The acid dependence usually has been associated with the bromine chemistry of reactions R1–R5.…”
Section: Introductionmentioning
confidence: 75%
“…The reaction products were found to be BrMeMA and acetic acid (AcA), in the ratio 2:3 respectively, exactly as was predicted by FKN for MA. Jwo and others have investigated the kinetics of ethyl-, butyl-, phenyl-malonic acids, and many similar species [79][80][81][82][83]. These acids are less reactive than MA with Ce 4+ , and typically form less reaction products.…”
Section: (I)mentioning
confidence: 94%